2009
DOI: 10.1002/pat.1245
|View full text |Cite
|
Sign up to set email alerts
|

Selective precipitation of plasmid with a water‐soluble cationic surfactant

Abstract: The aim of the present study was the selective precipitation of plasmid directly from alkaline lysate produced from bacterial culture with the cationic detergent, N, N', N'‐polyethylene (10)‐N tallow‐1, 3‐di amine propane. Polyethylene groups of peg‐10 tallow were functionalized with tertiary amine groups and long alkyl chain. The functional groups of cationic detergent were determined by means of 1H nuclear magnetic resonance (NMR) spectroscopy. A simple and efficient process for plasmid purification by catio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This topic has gained more and more interest because of its involvement either for plasmid purification 12 or in gene therapy processes. 13 Indeed, gene delivery has been developed to modify or regulate gene sequences and to treat various diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This topic has gained more and more interest because of its involvement either for plasmid purification 12 or in gene therapy processes. 13 Indeed, gene delivery has been developed to modify or regulate gene sequences and to treat various diseases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In our previous paper [15], it was found that N, N', N'-Polyethylene (10)-N tallow-1,3 di amine propane (PEG-10 tallow) cationic surfactant is usable for the selective precipitation of plasmid DNA directly from alkaline lysate. Cationic PEG-10 tallow has long-chain (C 12 -C 18 ) tertiary amines combined with 10 moles poly (oxyethylene) (POE) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Cationic PEG-10 tallow has long-chain (C 12 -C 18 ) tertiary amines combined with 10 moles poly (oxyethylene) (POE) [15,16]. However, no reports appear available on the CMC of PEG-10 tallow under different conditions.…”
Section: Introductionmentioning
confidence: 99%